Vardagligt samspel och mobila sängar i barnstorlek – en visuell historisk analys av vilan i förskolan - Grunditz, Sofia; Lindgren, Anne-Li; Frankenberg, Sofia (Educare, 2019)
In previous historical studies on preschools, the main sources are texts; photos are used merely as illustrations. Inspired by the idea to use visual materials to study the look of the past by scrutinising historical photos and films of naptime in preschool, this article will shed light on preschool as an institution and on the materiality of naptime practices. The data comprise of historical photographs and films from the period 1900–1970 (in total 14 films and approximately 200 photographs that, in one way or the other, depict naptime: adult and child interaction, the beds' constructions, the material organization of rooms and naptime routines). By using visual analyses, visualizations and the notion of path dependence, the article shows how the everyday practice of napping was carried out in the historical preschool in relation to questions of continuity and change. The results suggest that the design of beds, as child-sized and easy to move and store, can be understood as defining the institution as a preschool with play and educational practices as its main purpose. At the same time, however, the beds themselves indicate that care, as sleep or napping, was an essential practice in historic preschools.